Measuring the Intention for Innovative Work Behavior: Scale Development for Indonesian Employees - Etikariena, Arum; Kusuma, Aflaha Hadini; Dewi, Anak Agung Istri Ratna Kumala; Shabrina, Devika Nur; Hafizhah, Rana; Seno, Zidan Raleto (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
The current business era is dynamic and filled with uncertainty, and innovating is no longer an option but a solution to survive and compete. Innovation in the organisational context is displayed by employees in their work, known as Innovative Work Behaviour (IWB). However, the measurement tool for innovative work behavior focuses on past behavior, whereas innovative behavior is characterized by uncertainty. Previous behavior may not necessarily predict future behavior. Meanwhile, intention is the closest factor to predicting future behavior. Some researchers have adjusted the measurement of innovative work behavior into the intention for innovative work behavior. But its reliability and validity have not been tested, and it has not been adapted to the Indonesian language. Therefore, this quantitative study aims to develop a measurement tool of intention for innovative work behavior in Indonesia based on the Su et al. Scale (2019). Using the convenience sampling method, 1,071 participants who had worked for at least 1 (one) year in their organisation participated in this study. The results show that the I-IWB Scales had good reliability (α = 0.840). Confirmatory factor analysis also revealed that the scale fit the one-factor model (RMSEA = 0.054 < 0.070; 90% CI 0.044, 0.066), (CFI = 0.970 > 0.950), (TLI = 0.955 > 0.900). Construct validity shows the model fit as a unidimensional scale. Thus, based on the analysis results, it can be said that the I-IWB Scale is still reliable and valid for measuring the construct of intention for innovative work behaviour for Indonesian employees.